2008
DOI: 10.1155/2008/269097
|View full text |Cite
|
Sign up to set email alerts
|

Object-Place Recognition Learning Triggers Rapid Induction of Plasticity-Related Immediate Early Genes and Synaptic Proteins in the Rat Dentate Gyrus

Abstract: Long-term recognition memory requires protein synthesis, but little is known about the coordinate regulation of specific genes. Here, we examined expression of the plasticity-associated immediate early genes (Arc, Zif268, and Narp) in the dentate gyrus following long-term object-place recognition learning in rats. RT-PCR analysis from dentate gyrus tissue collected shortly after training did not reveal learning-specific changes in Arc mRNA expression. In situ hybridization and immunohistochemistry were therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 76 publications
(78 reference statements)
3
43
0
2
Order By: Relevance
“…One widely studied candidate gene is the early growth response gene-1 (EGR-1; also known as zif-268, NGFI-1, Krox-24), a member of a family of zinc finger inducible transcription factors that is believed to be critical for regulating the transcription of late-response genes that promote functional and/or structural changes underlying long-term synaptic plasticity and memory formation (Davis et al 2003;Knapska and Kaczmarek 2004). In other memory systems, EGR-1 has been implicated in long-term forms of experience-dependent synaptic plasticity (Cole et al 1989;Richardson et al 1992;Abraham et al 1993;Bramham et al 1996;Davis et al 2000;Jones et al 2001;Håvik et al 2003;Renaudineau et al 2009) and in memory formation, including song learning in songbirds, in vitro eye-blink conditioning in turtles, and in object recognition memory and spatial learning in rats (Mello and Clayton 1994;Jones et al 2001;Bozon et al 2003a;Mokin and Keifer 2005;Soulé et al 2008). Recent studies have also implicated EGR-1 in memory reconsolidation processes, including those associated with contextual fear conditioning in the hippocampus (Lee et al 2004;Lee 2008) and cue-induced drug seeking in the amygdala (Lee et al 2006).…”
mentioning
confidence: 99%
“…One widely studied candidate gene is the early growth response gene-1 (EGR-1; also known as zif-268, NGFI-1, Krox-24), a member of a family of zinc finger inducible transcription factors that is believed to be critical for regulating the transcription of late-response genes that promote functional and/or structural changes underlying long-term synaptic plasticity and memory formation (Davis et al 2003;Knapska and Kaczmarek 2004). In other memory systems, EGR-1 has been implicated in long-term forms of experience-dependent synaptic plasticity (Cole et al 1989;Richardson et al 1992;Abraham et al 1993;Bramham et al 1996;Davis et al 2000;Jones et al 2001;Håvik et al 2003;Renaudineau et al 2009) and in memory formation, including song learning in songbirds, in vitro eye-blink conditioning in turtles, and in object recognition memory and spatial learning in rats (Mello and Clayton 1994;Jones et al 2001;Bozon et al 2003a;Mokin and Keifer 2005;Soulé et al 2008). Recent studies have also implicated EGR-1 in memory reconsolidation processes, including those associated with contextual fear conditioning in the hippocampus (Lee et al 2004;Lee 2008) and cue-induced drug seeking in the amygdala (Lee et al 2006).…”
mentioning
confidence: 99%
“…In fact, it has been demonstrated that the inhibition of miR-132 attenuates spine formation and dendritic plasticity through a down regulation of P250 GAP Miller et al, 2012;Vo et al, 2005;Wayman et al, 2008). Synaptic proteins, including PSD-95, in the synaptic region critically regulate synaptic plasticity (Soulě et al, 2008). It has been stated that PSD-95 expression is epigenetically regulated by CREB and is critically involved in synaptic plasticity (Ehrlich et al, 2007;Meyer, Bonhoeffer, & Scheuss, 2014;Pollak et al, 2005;Wang, Yan, Hui, & Zhang, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…7 Further, like DA, brain-derived neurotrophic factor (BDNF) is another major neurochemical that promotes cell survival, neural outgrowth, differentiation, plasticity and regeneration of damaged neurons sprouting through Trkβ R activation, and modulation of chemical synapses. 8,9 Evidences suggest that nicotine induces BDNF and upregulates BDNF R (Trkβ) in rat brain. 10 Acute Trkβ activation potentiates presynaptic DA release and transport in different brain regions.…”
Section: Introductionmentioning
confidence: 99%